HISTORICAL AND MODERN CLASSIFICATION OF PROVERBS (American Journal of Pedagogical and Educational Research, 2023)
Since the formation of paralinguistics as a science, many studies have been conducted to this day. During the work carried out by scientists, different approaches to the issue of classification in the field are considered. Naturally, each researcher has his or her own views on these views. In this article, the paralinguistic classification is analyzed from the point of view of historians of modern and contemporary linguistics. In this process, we aimed to conduct a comparative analysis of the paralinguistic classifications cited by some researchers.